2022
DOI: 10.1096/fj.202101905rr
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of the pharmacological cold mimetic menthol stimulates brown adipose tissue thermogenesis through a TRPM8, UCP1, and norepinephrine dependent mechanism in mice housed at thermoneutrality

Abstract: Increasing whole-body energy expenditure via the pharmacological activation of uncoupling protein 1 (UCP1)-dependent brown adipose tissue (BAT) thermogenesis is a promising weight management strategy, yet most therapeutics studied in rodents to date either induce compensatory increases in energy intake, have thermogenic effects that are confounded by sub-thermoneutral housing temperatures or are not well tolerated in humans. Here, we sought to determine whether the non-invasive topical application of the pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 85 publications
(186 reference statements)
0
6
0
Order By: Relevance
“…A series of studies have revealed that the browning of subcutaneous WAT has the potential to combat obesity and metabolic disorders through oxidating glucose and lipid substrates in the form of nonshivering thermogenesis [21,22] . However, the present strategies targeting at inducing the browning of subcutaneous WAT, including topical cold treatment and microneedle-mediated rosiglitazone release system, are limited by the possible side effects, complex operation processes or unendurable high cost [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have revealed that the browning of subcutaneous WAT has the potential to combat obesity and metabolic disorders through oxidating glucose and lipid substrates in the form of nonshivering thermogenesis [21,22] . However, the present strategies targeting at inducing the browning of subcutaneous WAT, including topical cold treatment and microneedle-mediated rosiglitazone release system, are limited by the possible side effects, complex operation processes or unendurable high cost [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Cold exposure (8-26 C) and compounds such as menthol activate TRPM8 channels [21,29]. Activation of TRPM8 channels by topical menthol administration has previously been shown to increase thermogenesis and reduce weight gain in HFD-fed mice [30][31][32]. To test the role of TRPM8 channels on HDAC expression in adipose tissue, we treated thermoneutral-housed CD-fed mice with topical menthol.…”
Section: Activation Of Cold-sensitive Trpm8 Channels Downregulates Hd...mentioning
confidence: 99%
“…Menthol also has a weak therapeutic effect on obesity. DIO mice lost 1.6% BW after menthol treatment at 2 g/kg (s.c.) once daily for five consecutive days over 2 weeks (McKie et al, 2022).…”
Section: Terpenoids In Obesity Pharmacotherapiesmentioning
confidence: 99%
“…Menthol has been identified as a potent agonist of the transient receptor potential melastatin 8 (TRPM8) channel (Xu, Han, et al, 2020) to increase EE in rats (Vizin et al, 2018) and mice (Ma et al, 2012; McKie et al, 2022). Menthol could induce BAT thermogenesis by up‐regulating UCP1 expression via the Ca 2+ ‐dependent protein kinase A (PKA) phosphorylation (Ma et al, 2012) and via TRPM8‐norepinephrine‐β3AR signaling (McKie et al, 2022).…”
Section: Terpenoids In Obesity Pharmacotherapiesmentioning
confidence: 99%
See 1 more Smart Citation